A four-part series on the development and ethical issues of the local beauty industry. - Wong, Sher Maine. (2009)
Local celebrity Benedict Goh recently went from looking beautiful to making others look beautiful. The ex-host of the popular television game show, The Pyramid Game, made headlines when he left the Television Corporation of Singapore (TCS) abruptly a few months ago to set up his one-man beauty salon, Global Esthetics, at Ming Arcade. His move, amongst other personal factors, was partly due to the fact that the local beauty industry is a profitable one.